Աշխարհի պատկերն ըստ Հովհաննես Թումանյանի - Խաչատրյան, Թադևոս (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Творческое наследие Ованеса Туманяна занимает важнейшее место в армянской литературе и во всей духовной культуре. Творчество поэта стало наилучшим воплощением прошлого и настоящего Армении, ее духовных сил и художественных традиций. То обстоятельство, что Туманян творил на стыке двух столетий – XIX и XX веков – может стать отправной точкой для изучения философского контекста его творчества. В целом его можно представить как систему представлений о действительности, с помощью которых можно выделить, описать или реконструировать любую социально-психологическую единицу, будь то нация, социальная группа или индивид. Creative heritage of Hovhannes Tumanyan occupies the most important place in the Armenian literature and in the entire spiritual culture. The poet's creative works has become the best embodiment of the past and present of Armenia, its spiritual power and artistic traditions. The fact that Tumanyan created at the turn of two centuries – XIX and XX centuries – can be the starting point for studying the philosophical context of his works. In general, it can be represented as a system of insightful perceptions of reality, with the help of which one can single out, describe or reconstruct any social-psychological unit, whether it be a nation, a social group or an individual.
Keywords: Գրականագիտություն